2015
DOI: 10.1186/s12974-015-0279-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the spinal astrocytic JNK/MCP-1 pathway activation correlates with the analgesic effects of tanshinone IIA sulfonate in neuropathic pain

Abstract: BackgroundNeuropathic pain (NP) continues to be challenging to treat due to lack of effective drugs. Accumulating evidence elucidated that glia-mediated inflammatory reactions play a pivotal role in the introduction and development of NP. Besides, activation of the c-Jun N-terminal kinase (JNK)/monocyte chemoattractant protein-1 (MCP-1) pathway in astrocytes has been reported to be critical for spinal astrocytic activation and neuropathic pain development after spinal nerve ligation (SNL). Tanshinone IIA, a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…35 Besides, it has been proven that MCP-1 is produced by astrocytes via the JNKmediated signaling pathway. 36 However, we provided evidence that the JNK and Wnt/β-catenin signaling pathways could be activated by MCP-1. Besides, MCP-1 enhanced LPS-induced injury possible via regulating these two signaling.…”
Section: Discussionmentioning
confidence: 85%
“…35 Besides, it has been proven that MCP-1 is produced by astrocytes via the JNKmediated signaling pathway. 36 However, we provided evidence that the JNK and Wnt/β-catenin signaling pathways could be activated by MCP-1. Besides, MCP-1 enhanced LPS-induced injury possible via regulating these two signaling.…”
Section: Discussionmentioning
confidence: 85%
“…Briefly, rats were placed on a cylinder and then the rotational speed was gradually accelerated from 4 to 40 rpm in 5 min. Latency to fall off in three repeated trials was recorded according to previous studies 2325…”
Section: Methodsmentioning
confidence: 99%
“…However, it is primarily expressed in astrocytes [61,125,158-160]. In 2006, Zhuang and collaborators demonstrated that a spinal injection of a JNK inhibitor, D-JNKI-1JNK, prevented mechanical allodynia in SNL-exposed animals, and this effect was correlated with astrocyte suppression [61].…”
Section: Mitogen-activated Protein Kinase (Mapk)mentioning
confidence: 99%